Bacterial Toxin‐Responsive Biomimetic Nanobubbles for Precision Photodynamic Therapy against Bacterial Infections (Adv. Healthcare Mater. 18/2022). Issue 18 (20th September 2022) - Zhuge, Deli; Li, Li; Wang, Haonan; Yang, Xuewei; Tian, Dongyan; Yin, Qingqing; Chen, Hao; Weng, Cuiye; Wen, Bin; Lin, Yijing; Huh, Joo Young; Zhang, Xufei; et al.
Abstract : Bacterial Infections Secreted bacterial toxins such as pore‐forming toxins (PFTs) are capable of governing the photodynamic therapy (PDT) effect of RBC(IR780)‐PFC(O2 ) nanobubble for treatment of source bacterial infections. Leveraging this unique approach, Mengchun Chen, Congying Xie, Yingzheng Zhao, Yijie Chen, and co‐workers in article 2200698 are able to transform what would normally be considered a negative aspect of bacterial infections (i.e., toxin secretion) into a positive aspect.